1997
DOI: 10.1016/s0006-3495(97)78755-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of six different fully hydrated monomeric conformers of Escherichia coli re-lipopolysaccharide in the presence and absence of Ca2+

Abstract: Six previously published conformational models of Escherichia coli Re lipopolysaccharide (ReLPS) were subjected to molecular dynamics simulations using the CHARMM force field. The monomers of ReLPS were completely immersed in a water box. The dynamic behavior of the solvated models in the presence and absence of calcium cations was compared. The structure of the solvent shell was analyzed in terms of radial distribution functions. Diffusion coefficients and mean residence times were analyzed to characterize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 69 publications
4
32
0
Order By: Relevance
“…Under these conditions LPS aggregate stability is apparently decreased by Ca 2+ binding to PO 4 − in the lipid A region. This is in agreement with previously published studies on rough LPS [9,24,53]. We postulate that Na-LPS aggregates interact with the ZnSe IRE, whereas Ca-LPS aggregate disruption results in LPS monomer interaction via hydrophobic mechanisms.…”
Section: Ca-lps Interactionssupporting
confidence: 93%
See 1 more Smart Citation
“…Under these conditions LPS aggregate stability is apparently decreased by Ca 2+ binding to PO 4 − in the lipid A region. This is in agreement with previously published studies on rough LPS [9,24,53]. We postulate that Na-LPS aggregates interact with the ZnSe IRE, whereas Ca-LPS aggregate disruption results in LPS monomer interaction via hydrophobic mechanisms.…”
Section: Ca-lps Interactionssupporting
confidence: 93%
“…Specifically, it has been suggested that an increase in LPS aggregation [19][20][21][22] might result when Ca 2+ -rather than Na + -is present because of the high stability of Ca 2+ complexation with phosphate moieties of the lipid A region. If so, that would be expected to affect surface interactions of the macromolecules [14,19,23,24]. Our previous studies using attenuated total reflectance (ATR) Fourier transform infrared (FTIR) spectroscopy do indeed provide direct evidence of Ca 2+ binding to LPS phosphate groups, but also suggest a more complex effect on aggregate structure [11].…”
Section: Introductionmentioning
confidence: 90%
“…(The conformation of the polysaccharide chain of LPS was also estimated by energy minimization, with the result that O chains were predicted to be bent strongly against the membrane normal [325].) The energy minimization approach predicted several different conformers of Re LPS (326), and molecular dynamics simulation of single LPS molecules preserved the initial conformation (469). The next important step, the simulation of the LPS aggregate, an effort that required 3 months of computer time, was performed by Kotra et al (350).…”
Section: What Makes the Lps Leaflet An Effectivementioning
confidence: 99%
“…Molecular modeling studies of bacterial surfaces (e.g., lipopolysaccharide structures associated with the cell membranes of gram-negative bacteria) have been completed over the past decade (Kastowsky et al, 1992;Wang and Hollingsworth, 1996;Obst et al, 1997;Kotra et al, 1999;Lins and Straatsma, 2001;Shroll and Straatsma, 2003). These studies have used various levels of atomic abstractions and classical molecular mechanics to evaluate the structure and dynamics of the complex surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have used various levels of atomic abstractions and classical molecular mechanics to evaluate the structure and dynamics of the complex surfaces. Previous research includes Shroll and Straatsma (2003) employing classical molecular simulation techniques to model the adhesion of Pseudomonas aeruginosa to the mineral goethite, and Obst et al (1997) examining the impact of Ca 2+ on the lipopolysaccharide structure of Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%